2006
DOI: 10.1111/j.0022-1112.2006.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Photopigment spectral absorbance of Lake Malaŵi cichlids

Abstract: To predict spectral sensitivity, microspectrophotometry (MSP) was used to measure absorbance of photoreceptor cells from 15 species of Lake Malaŵ i cichlids. Each fish had one rod and at least three cone pigments. UV-sensitive pigments were common, but spectral sensitivity did not clearly correlate with feeding mode or habitat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 27 publications
7
50
1
Order By: Relevance
“…In all five species, double cones were similar, usually consisting of one cone cell containing a visual pigment with  max near 480nm and a second cone with a visual pigment with  max near 530nm. In three species, single cone pigments were ultraviolet sensitive, whereas the remaining two species had violetsensitive single cones (Carleton et al, 2000;Jordan et al, 2006;Levine and MacNichol, 1979;Parry et al, 2005). Based on these results, we conclude that rock-dwelling cichlids of Lake Malawi have one of two basic types of colour vision systems that substantially differ only in short wavelength sensitivity.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In all five species, double cones were similar, usually consisting of one cone cell containing a visual pigment with  max near 480nm and a second cone with a visual pigment with  max near 530nm. In three species, single cone pigments were ultraviolet sensitive, whereas the remaining two species had violetsensitive single cones (Carleton et al, 2000;Jordan et al, 2006;Levine and MacNichol, 1979;Parry et al, 2005). Based on these results, we conclude that rock-dwelling cichlids of Lake Malawi have one of two basic types of colour vision systems that substantially differ only in short wavelength sensitivity.…”
Section: Introductionmentioning
confidence: 72%
“…M. heterochromis (previously M. vermivorus) MSP data are from Parry et al (Parry et al, 2005), M. zebra SWS1 and RH2 MSP results are from Carleton et al (Carleton et al, 2000) and Levine and MacNichol (Levine and MacNichol, 1979), respectively, and the remaining MSP data are from Jordan et al (Jordan et al, 2006). All measurements are in nm.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, fish with three cone classes would do better than those with two, but humans would still be able to reconstruct the colour The Journal of Experimental Biology 216 (9) signals better. Many coral reef fish were suggested to display two cone classes (Losey et al, 2003) while many African cichlids were suggested to typically display three cone classes (Jordan et al, 2006;Carleton et al, 2008). Our results indicate that using two or three cone classes in these fish would lead to a reduced accuracy of coloursignal reconstruction compared with that of humans.…”
Section: Dimensionality Of Colour Vision In Fishmentioning
confidence: 78%
“…For example, zebrafish (Danio rerio) display seven cone pigments (Vihtelic et al, 1999;Chinen et al, 2003); guppies (Poecilia reticulata) (Archer and Lythgoe, 1990) and killifish (Lucania goodei) (Fuller et al, 2003) display five cone pigments; salmonids (Salmonidae) (Hawryshyn and Hárosi, 1994;Temple et al, 2008) display four to six cone pigments; black bream (Acanthopagrus butcheri) (Shand et al, 2008), goldfish (Carassius auratus) (Hawryshyn and McFarland, 1987;Neumeyer, 1992) and three-spine stickleback (Gasterosteus aculeatus) (Rowe et al, 2004) display four cone pigments; coral reef fish display two to four cone pigments Losey et al, 2003); and African cichlids typically display three cone pigments (Jordan et al, 2006;Carleton et al, 2008), although several species were shown to display up to seven pigments (Parry et al, 2005). However, the presence of a large number of cone pigments in the retina may not necessarily suggest the possession of high-dimensional colour vision.…”
Section: Introductionmentioning
confidence: 99%